Equality Of The Sexes? - Haughton, Emma. (North Mankato, MN : Sea to Sea Publications, 2006)
An illustrated title in the VIEWPOINTS series, which discusses the issue of the rights of men and women in modern society, accompanied by quotes from well known figures, to provide insight into a range of viewpoints. Compatible with National Curriculum Key Stage 3.
Originally published: New York : Franklin Watts, 1997. (Viewpoints)
Includes index.
Keywords: Sexism -- Juvenile literature; Women's rights -- Juvenile literature; Sex role -- Juvenile literature